Prophylactic Sublay Mesh Placement During Stoma Closure to Prevent Incisional Hernias: a Pilot Study - Yana Belenkaya; Sergey Gordeev; Nikolay Matveyev; Zaman Mamedli (Turkish Journal of Colorectal Disease)
Introduction: There are many methods to prevent hernia following stoma closure; however, there is a lack of evidence of the efficacy of prophylactic sublay synthetic mesh placement. This study aimed to investigate the safety of sublay mesh placement during stoma closure. Methods: Patients with rectal cancer who underwent stoma closure with prophylactic sublay mesh placement following low anterior resection at N.N. Blokhin Cancer Research Center between June and July 2023 were included in this pilot study. The inclusion criteria were age 18-75, TNM stage I-III, and written informed consent. The exclusion criteria included patients with synchronous and metachronous cancers, human immunodeficiency virus, an Eastern Cooperative Oncology Group score of >2, and those undergoing chemotherapy. The sublay mesh placement technique was used, with the endpoints being surgical site infection rate at 30 days, operative time, mesh placement time, and postoperative morbidity (Clavien-Dindo classification). Results: Ten patients were included in the study. Among them, one patient (10%) had a postoperative surgical site infection, which did not require mesh removal. There was no other morbidity. The median operative time was 105.5 min, whereas the median mesh placement time was 25.5 min. Conclusion: A low surgical site infection rate makes it possible to consider preventive sublay mesh placement during stoma closure. We initiated a prospective randomized clinical trial after this pilot study (ClinicalTrials.gov, NCT05939687).